FIRST REPORT OF A MARINE DINOFLAGELLATE, ALEXANDRIUM ANDERSONII (DINOPHYACEAE) IN MALAYSIAN WATERS - Mohd Razali, Roziawati; Chui-, Pin Leaw2; Hong-, Chang Lim; Ayub, Mohd Nor Azman; A. Rahim, Masazurah; Po-, Teen Lim (Malaysian Journal of Science, 2016)
A field survey was carried out at aquaculture areas of Aman Island, Penang to monitor harmful microalgae. In this study, a strain of Alexandrium species was established in laboratory culture and identified using morphological criteria and nucleotide sequences of the LSU rDNA to confirm the identification. The strain was observed under epi-fluorescence microscope and the morphological characters resembled to the species description of A. andersonii. Based on the nucleotide sequences, the strain also revealed close relationship to A. andersonii. HPLC analysis found that A. andersonii was not able to produce paralytic shellfish toxins. This is the first report of A. andersonii found in Malaysian waters. Kajian lapangan telah dijalankan di kawasan akuakultur Pulau Aman, Pulau Pinang untuk memantau mikroalga berbahaya. Dalam kajian ini, strain spesis Alexandrium telah dikultur di makmal dan pengesahan identifikasi spesis adalah berdasarkan morfologi dan jujukan nukleotida, LSU rDNA. Strain tersebut diperhati di bawah mikroskop epi-pendarfluor dan didapati ciri morfologinya adalah menyerupai spesis A. andersonii. Berdasarkan jujukan nukleotida, strain ini juga didapati mempunyai hubungan rapat dengan A. andersonii. Analisa HPLC mendapati bahawa A. andersonii tidak menghasilkan toksin paralitik. Ini merupakan laporan pertama A. andersonii dijumpai di perairan Malaysia. Keywords: Alexandrium, morphology, LSU rDNA, PSP toxins